Heavy Coffee Consumption and Risk of Pancreatitis: A Systematic Review and Meta-Analysis - Karn Wijarnpreecha (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. Background/Objectives: Heavy consumption of coffee may have a protective effect against pancreatitis although results from previous studies were inconsistent. This meta-analysis was conducted with the aim to summarize all available data. Methods: This meta-analysis included observational studies that compared the risk of pancreatitis between heavy coffee-drinkers and individuals who were not heavy coffee-drinkers. Pooled risk ratios (RRs) and 95% confidence interval (CI) were calculated using a random-effect, generic inverse variance method. Results: Out of 219 retrieved articles, four studies with 351,137 participants met the eligibility criteria and were included in the analysis. The risk of pancreatitis among heavy coffee-drinkers was significantly lower than individuals who were not heavy coffee-drinkers with the pooled RR of 0.78 (95% CI 0.67–0.91). The statistical heterogeneity between the studies was insignificant (I2= 0%). Conclusions: This meta-analysis demonstrated a significantly decreased risk of pancreatitis among heavy coffee-drinkers. However, further investigations are still required to determine causality and potential clinical application.